LIFELONG LEARNING AS A VALUE - Balceraite, Lasma; Lubkina, Velta; Usca, Svetlana (Education Reform: Education Content Research and Implementation Problems, 2022)
Due to changes in the labour market over the last thirty years adult education has developed significantly. Adult education is becoming an integral part of every person’s life and advancement towards certain goals. Many adults attempt to learn independently, by using information technology. During the Covid-19 pandemic, educational processes could only continue in e-environment, using e-platforms (Zoom, Microsoft Team, etc.) or blended learning (a mix of face-to-face lessons and lessons on e-platforms).The study was carried out within the framework of the Master`s Thesis “Transformation of Educational Values in Lifelong Learning”. Aim of the research: to seek the views of the Latvian population on the current educational values in lifelong learning in order to compare them in the period before and after the Covid-19 pandemic.The paper analyses scientific literature and research; analytical reasoning is based on the results of the questionnaire.